Fanconi Syndrome and Osteomalacia Induced by Tenofovir - Lissa Sabrina; Sidharta Salim (Cermin Dunia Kedokteran, 2024)
Introduction: Tenofovir disoproxil fumarate (TDF), an antiviral nucleoside analog reverse transcriptase inhibitor, has been used for the treatment of HIV and HBV in the past decades. TDF nephrotoxicity has been reported and could lead to renal failure and Fanconi Syndrome (FS). Case: A 58-year-old female HBsAg carrier with TDF treatment since 2013 presented with osteomalacia. She had glucosuria, albuminuria, vitamin D insufficiency, hypophosphatemia, and occasional hypokalemia episodes. Laboratory results showed amino aciduria, which indicates renal tubulopathy. The diagnosis of Fanconi syndrome was confirmed. Withdrawal of TDF was followed by improvement. Conclusion: The acquired FS associated with TDF is reversible. The use of TDF-containing antiviral regimens should be followed by screening recommendations to detect early Fanconi syndrome.